Pengembangan Situs Web Untuk Promosi Warisan Budaya Lokal dan Pariwisata Berbasis Berita - Ramadhani, Rachmad; Setiawan, Eman (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2024)
In the modern era dominated by technology and information, the development of news-based websites has emerged as a key element in supporting the promotion of tourism and cultural heritage in tourist destinations. This research investigates how news-based websites can be a key factor in enhancing tourism promotion, as well as the key elements that need to be considered to ensure their effectiveness in attracting visitor and supporting tourism destination promotional objectives. In addition, this research also examines methods for measuring the success of tourism and cultural promotion websites in achieving promotional objectives, including increasing the number of visitors and participation in cultural activities. The role of news content in enhancing website attractiveness and driving user interaction is also the focus of the analysis. Furthermore, this research explores users' experiences and their interactions with news-based websites in tourism. Factors influencing user preferences and participation are also analyzed to understand how to increase the effectiveness of news-based websites in the context of tourism and culture promotion. The results of this research provide important insights for the development and improvement of news-based tourism and culture promotion websites, as well as a greater contribution to sustainable tourism development and preservation of local cultural heritage.